A - Brazil, David (Oxford University Press, 1995)
Using authentic, naturally-occurating data, this book provides an innovative anlysis of the grammar of spoken English. It proceeds from an understanding that speakers and listeners bring to every piece of purposeful discourse a complex bacground of shared understandings which inform their interaction